Contribuição ao estudo químico de espécies da família Cucurbitaceae juss. e Rubiaceae juss. gêneros: Cayaponia Silva Manso e Psychotria L. - Lemes, Geralda de Fátima (2015)
This work describes the chemical evaluation and, in parallel, the investigation of antioxidant and antimicrobial activity of four medicinal species of Brazilian Cerrado, Cayaponia espelina (Silva Manso) Cogn., C. citrullifolia (Griseb.) Cogn., C. weddellii (Naudin) Gomes-Klein (Cucurbitaceae) and Psychotria trichophora Müll. Arg. (Rubiaceae). The study of ethanol extracts of the species mentioned above led to the isolation of several classes of secondary metabolites, many of them presenting biological activity. Evaluation of ethyl acetate fractions of the leaves of C. espelina and n-butanol and hydromethanol fractions of C. citrullifolia led to the isolation and structural elucidation of seven compounds: luteolin (CE- 1), luteolin 4'-O-glucoside (CE-2), luteolin 7-O-glucoside (CE-3), kaempferol 3,7- O-α-L-dirhamnoside (CC-1), benzyl-O-β-D-xylopyranosyl-(1→6)-β-Dglucopyranoside (CC-4), salicylic acid 2-O-β-glucopyranoside (CC-3) and vicenin-2 (CC-2). The glucosides CE-2 and CE-3 found in C. espelina were also found in ethyl acetate fraction from C. weddellii leaves, indicating that there might be a chemical similarity between these species. The fourth species investigated in this study was P. trichophora and the chemical study of ethyl acetate fraction of its leaves led to the isolation and structural elucidation of six compounds: camelliaside B (PT-3), kaempferol-3-O-α-L-rhamnopyranosyl-(1→6)-[β-Dxylopyranosyl-( 1→2)]-β-D-galactopyranoside (PT-4), kaempferol-3-O-[β-Dxylopyranosyl-( 1→3)-α-L-rhamnopyranosyl-(1→6)]-β-D-galactopyranoside (PT- 5), kaempferol-3-O-robinoside (PT-2) and 3-O-p-coumaroylquinic acid (PT-6). Coumarin scopoletin (PT-1) were identified from its roots. Structural identification of compounds was performed by spectroscopic analysis including IR and 1H and 13C NMR, in one-and two-dimensions. Flavonoids PT-4 and PT-5, previously isolated in the Fabaceae and Leguminosae families, were described for the first time in Rubiaceae. Furthermore, CCDA analysis of acid-base fractions obtained from P. trichophora leaves did not result positive for alkaloids against the Dragendorff reagent. Preliminary tests in Escherichia coli showed that the ethyl acetate fraction from C. espelina presents pharmacological potential, inhibiting 74 % of bacterial growth at a 82 μg/mL concentration. This fraction also exhibited strong antioxidant activity, with IC50 value of 5.40 ± 0.16 μg/ml, being comparable to that of the commercial antioxidant, ascorbic acid. Extracts from C. espelina and C. weddelli were the most promising antioxidants with IC50 values of 131 ± 0.31 and 13.14 ± 0.57 μg/mL, respectively. In preliminary bioassays against Sarcoma 180 tumor cell line, all tested samples presented low activity despite the literature data for antitumor activity of the isolated flavonoids.